Evaluation of Supraclavicular Brachial Plexus Nerve Block with Patient Controlled Intravenous Analgesia for Post-Operative Pain Management in Patients with Forearm Surgery - Ahmed, Mushtaq; Ahmad, Ashfaq; Ali, Amjad; Tabani, Kashif Iqbal; Tunio, Muhammad Zaib; Shah, Saqib (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the efficacy of supraclavicular brachial plexus block with patient-controlled intravenous analgesia (PCIA) for post-operative pain management in forearm surgery. Study Design: Comparative Cross-Sectional Study. Place and Duration of Study: Department of Anesthesia, Combined Military Hospital, Kharian Pakistan, from Sep 2018 to Nov 2019. Methodology: Eighty-two adult patients, of ASA Class I and II, were enrolled and were randomly divided into two equal groups using computer-generated random numbers. General anaesthesia was administered to both groups. Additionally, Group-A (n=41) received supraclavicular brachial plexus block while Group-B (n=41) received patients-controlled analgesia. Post-operative pain was assessed using a 10 cm visual analogue scale (VAS). The pain scores were noted after complete recovery from general anaesthesia at 5 minutes, 6, 12 and 24 hours. Results: The pain score was found to be significantly lower in Group-A (supraclavicular brachial plexus block) as compared to Group-B (patients-controlled analgesia) at 6, 12 and 24 hours (p<0.05) while the non-significant difference was noted at 5 minutes (p >0.05). Conclusion: Significantly, better pain control was noted in supraclavicular brachial plexus block compared to patients’- controlled analgesia in post-operative pain management.